INDIVIDUAL CAREER CHOICE AND ITS PEDAGOGICAL METHODOLOGY - Rafik Gayratovich Rahmatov (Bright Mind Publishing, 2025)
This article examines the relationship between an individual's career choice and the pedagogical methodologies used in adolescents' career decision-making. Drawing on psychological theories, educational models, and empirical data, this study examines how pedagogical practices such as career counseling, experiential learning, and guidance affect adolescents' career choices.
Keywords: Career choice, pedagogical methodology, career counseling, adolescent development, career guidance, career decision-making, psychological factors, sociocultural influences, models of upbringing.